Design and Fabrication of 6 Meter Fiberglass Boat for Coastal Water Tourism in Batam - Hendra Saputra; Danang Cahyagi; Veryawan Nanda Perkasa; Dedi Purnama; Oxa Nurmannsyah; Rangga Saputra; Regita Ferari; Faaza Ibnu Al Fauzy; Muhammad Fadillah (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
A tourist boat is one of the amenities frequently utilized in coastal water tourism activities in Batam. Boats used for tourism are frequently used for fishing or simply to take in the beauty of marine tourism. Thus, one of the requirements that must be developed for local tourism is the availability of boats for water tourism. The goal of this research is to create a design and prototype for a six-meter water tourism boat that can serve as a public reference within the same case study. Because of its advantages in terms of cost and readily available materials, fiberglass was selected as a material for design and fabrication. Because of its benefit of being a simple fabrication process, the fiber reinforced plastic method was also selected for use in the process. A six-meter fiberglass boat prototype was created through a multi-phase process that began with design, moved on to hydrostatic and power requirement prediction analyses, and ended with mold based fabrication. The study concludes that 40 horsepower (29.5 kW) is needed to power a 6-meter fiberglass boat that can accommodate five people and reach a maximum speed of 25 kN. Five to seven layers of fiberglass were used to successfully complete the ship fabrication process.